2013
DOI: 10.1177/1069072713515971
|View full text |Cite
|
Sign up to set email alerts
|

Does Trait Emotional Intelligence Predict Unique Variance in Early Career Success Beyond IQ and Personality?

Abstract: In order to determine the contribution of emotional intelligence (EI) to career success, in this study, we analyzed the relationship between trait EI (TEI), general mental ability (GMA), the big five personality traits, and career success indicators, in a sample of 130 graduates who were in the early stages of their careers. Results from hierarchical regression analyses indicated that TEI, and especially its dimension ''repair,'' has incremental validity in predicting one of the career success indicators (sala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
(65 reference statements)
6
14
0
1
Order By: Relevance
“…The purpose of the present study was to investigate the predictive and incremental validity of emotional intelligence over personality factors and proactive personality variables for career success (salary and job satisfaction) in a sample of early and later career graduates. Our findings confirmed the previously reported relationships between emotional intelligence and career success in different populations [44,59,60]. Our results also went beyond these previous findings, including some aspects that were not controlled in previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The purpose of the present study was to investigate the predictive and incremental validity of emotional intelligence over personality factors and proactive personality variables for career success (salary and job satisfaction) in a sample of early and later career graduates. Our findings confirmed the previously reported relationships between emotional intelligence and career success in different populations [44,59,60]. Our results also went beyond these previous findings, including some aspects that were not controlled in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Correlational analyses showed that emotional intelligence was positively corelated to both salary and job satisfaction. Regarding salary, our results were similar to the results of De Haro and Castejón [44], who found a positive correlation with emotional repair. The results generated by the relationship between emotional intelligence and job satisfaction were consistent with those found by previous studies [25,60,61].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These data show that abstract reasoning and learning abilities are not sufficient for achieving success in life; therefore, it has been proposed that emotional intelligence is the missing factor that predicts success and harnesses emotion to enable efficient problem solving (Brackett, Rivers, & Salovey, 2011). Human studies have shown that emotional intelligence, which can be assessed with emotion-based problem-solving tasks, is not only important for achieving personal success but is also crucial for mental health (Brackett et al, 2011;Garcıa & Costa, 2014;Hertel, Schutz, & Lammers, 2009;Quintana-Orts, Rey, Mérida-López, & Extremera, 2019). However, despite the importance of emotional intelligence, its biological mechanism is still not well understood.…”
Section: Introductionmentioning
confidence: 99%